The use of urinary purine derivatives to estimate microbial protein supply and feed intake - Şule Kaya (Eurasian Journal of Veterinary Sciences)
The urinary excretion of allantoin was first suggested as an index of rumen microbial protein yield about 30 years ago. Major progress towards establishing a method to relate purine derivatives excretion to microbial protein yield has only been made tn recent years. So that. the biochemistry of the purines. the factors effecting the amount ol purine derivatives excreted in the urine and the different approches to estimate recovery ol these denvatives originating from different sources has been explained in order to guide lor who is interested in this subject.